1993
DOI: 10.1182/blood.v82.4.1165.bloodjournal8241165
|View full text |Cite
|
Sign up to set email alerts
|

Selectin-mediated rolling of neutrophils on immobilized platelets

Abstract: Interaction between neutrophils and platelets at the site of vascular damage or in ischaemic tissue may promote thrombosis and/or vascular occlusion. To study this interaction, we have developed a novel technique that allows visualization of adhesion of flowing neutrophils to immobilized, activated platelets. The total number of adherent neutrophils decreased with increasing wall shear stress in the range 0.05 to 0.4 Pa. Although a proportion of the adherent neutrophils were stationary, most were rolling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 0 publications
3
68
0
Order By: Relevance
“…Our inability to block adhesion to IL‐1B‐treated HUVEC with antibodies against selectins is puzzling, even though there was clear upregulation of E‐selectin mRNA and surface expression as expected. The same antibodies against selectins have been effective in our previous studies in other adhesion models (Buttrum et al ., 1993; Rainger et al ., 1995; Bahra et al ., 1998; Rainger et al ., 1998). Others showed that blockade of L‐selectin or E‐selectin caused partial inhibition of adhesion of neutrophils to IL‐1B‐treated HUVEC in static or flow‐based assays (Bevilacqua et al ., 1987; Kishimoto et al ., 1991; Smith et al ., 1991; Abbassi et al ., 1993; Jones et al ., 1996), although the effects were not additive (Kishimoto et al ., 1991).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our inability to block adhesion to IL‐1B‐treated HUVEC with antibodies against selectins is puzzling, even though there was clear upregulation of E‐selectin mRNA and surface expression as expected. The same antibodies against selectins have been effective in our previous studies in other adhesion models (Buttrum et al ., 1993; Rainger et al ., 1995; Bahra et al ., 1998; Rainger et al ., 1998). Others showed that blockade of L‐selectin or E‐selectin caused partial inhibition of adhesion of neutrophils to IL‐1B‐treated HUVEC in static or flow‐based assays (Bevilacqua et al ., 1987; Kishimoto et al ., 1991; Smith et al ., 1991; Abbassi et al ., 1993; Jones et al ., 1996), although the effects were not additive (Kishimoto et al ., 1991).…”
Section: Discussionmentioning
confidence: 82%
“…In some experiments, neutrophils were treated with the platelet‐activating factor receptor (PAF‐R) antagonist YM264 (10 −4 M; Yamanouchi Pharmaceutical Co. Ltd, Tsukuba, Japan) for 3 min before assay. These agents have been effective in blocking function in our previous studies (Buttrum et al ., 1993; Rainger et al ., 1995; 1998; Bahra et al ., 1998).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Lacto‐N‐fucopentose (Lewis x , CD15) and sialyl‐Lewis x (CD15s) are also known to be possible ligands 30,38 . Differences in the degree of coaggregation of monocytes to neutrophil granulocytes may be explained by the different configuration of CD15 and CD15s, 25,39 and by the low affinity of the two antigens to CD62p 40 . In contrast to L‐selectin of neutrophil granulocytes, L‐selectin of lymphocytes does not express Le x and thus cannot serve as a receptor for P‐selectin 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Flowing neutrophils can roll on surfaces coated with purified P-selectin, histaminestimulated endothelial cells, or immobilized, activated platelets providing in vitro evidence for P-selectin-mediated neutrophil rolling (33,223,224) In addition, Table 4 summarizes these studies. leukocytes/slide using a light microscope at 630x oil immersion.…”
Section: Exteriorization Of Tissues In Preparation For Intravital Micmentioning
confidence: 99%